Maintaining price stability under free-floating: a fearless way out of the corner? - Carsten Detken; Vítor Gaspar (European Central Bank (ECB), 2003)
The behaviour of the exchange rate under a floating exchange rate regime for a small open economy with perfect capital mobility may appear like a managed float or even a firmer peg. We present a canonical new neo-classical synthesis open economy model where the central bank follows a strategy directed at maintaining price stability. It is shown that the behaviour of the exchange rate depends on the structure of the economy and on the nature of the relevant shocks. In the case of very open economies the exchange rate will look quasi-fixed in response to shocks stemming from the international capital markets. It is also shown that the joined endogeneity of the interest rate and the exchange rate has important implications for the empirical testing of uncovered interest rate parity.
Keywords: E58; E63; F41; 330; flexible exchange rates; managed floating; price stability; small open economy; uncovered interest rate parity